Використання штучного інтелекту для створення тривимірних моделей в ігровій індустрії - Лучной, С. В.; Кулішова, Н. Є. (ХНУРЕ, 2025)
This paper examines the application of artificial intelligence (AI) in the creation of three-dimensional models for the gaming industry. The study explores AI-based automated generation, texture enhancement, model detailing, and real-time adaptation. It highlights the benefits of generative adversarial networks (GANs) and machine learning techniques in accelerating and optimizing the modeling process. The research also discusses AI-driven procedural content generation, which allows for the automatic creation of realistic environments and objects in open-world games. The paper concludes by emphasizing the potential of AI in revolutionizing 3D modeling workflows and improving the efficiency of game development studios.
Keywords: тривимірна модель; ігрова індустрія